A Meta-Analysis of Neuron-Specific Enolase Levels in Cerebrospinal Fluid and Serum in Children With Epilepsy - Mu, Rong-Zheng; Liu, Shuang; Liang, Kai-Ge; Jiang, Dan; Huang, Yao-Jiang (Frontiers in Molecular Neuroscience, 2020)
BACKGROUND Studies suggest that neuron-specific enolase (NSE) levels in the cerebrospinal fluid (CSF) and serum play an important role in childhood epilepsy. However, these investigations remain controversial due to inconsistent clinical results. The present study aimed to quantitatively summarise and assess whether CSF and serum NSE levels are associated with epilepsy in children. METHODS A systematic search of the Harvard Hollis+, Clinicaltrials, Open Grey, China National Knowledge Infrastructure (CNKI) and Wanfang databases was performed. Studies investigating NSE and epilepsy were identified and retrieved. Original studies with data overlapping those from other investigations, and those lacking the necessary data were excluded. The included studies were extracted and synthesised, and data were analysed using a random-effects model in R Studio and Comprehensive Meta-Analysis version 3 (Biostat, Englewood, NJ, USA). RESULTS Random-effects meta-analysis of 26 studies, including 1360 patients and 1256 healthy control, revealed that childhood epilepsy exhibited meaningfully increased CSF and serum levels of NSE compared with controls (Hedges’ g 1.962 [95% CI 1.413–2.512]; P 0.001). No single study meaningfully influenced the overall association between CSF and serum levels of NSE and epilepsy after sensitivity analysis. Subgroup analyses according to sample source and assay type revealed a significant association between NSE levels and epilepsy. Stratified analysis confirmed that NSE levels were significantly correlated with the severity of neurological compromise. Meta-regression analyses revealed that sample size, mean age, and sex may contribute to effect-size reductions; however, sample source, assay type, and country did not moderate effect size. Funnel plots constructed using the trim-and-fill method confirmed that the outcome of the meta-analysis could not be due to publication bias. CONCLUSION The results demonstrated that childhood epilepsy exhibit significantly elevated levels of NSE in the CSF and serum, thus strengthening the association between increased NSE levels and epilepsy.